THE IMPACT OF OPENING UP A TRADITIONAL CULTURE TO TOURISM DEVELOPMENT - Caecilia, Caecilia; Umarjadi, Utami; Hidayat, Nila K. (Emerging Markets : Business and Management Studies Journal, 2015)
The Baduy Tribe is a cultured and friendly indigenous people living harmoniously in the middle of natural environment and far from the civilization. This study aims to determine the level of acceptance of opening up the Inner Baduy as a tourism destination and also to identify the impacts on the opening up the Inner Baduy to tourism development. This study use both quantitative and qualitative analysis. The result revealed that there are three elements are used to justify the level of acceptance of the Baduy people; two showed rejections (needs and desires and opinions on opening up the Inner Baduy). This is strengthened by the result of the interviews that tribe rules and regulations do not allow the Inner Baduy to be opened up. Another finding is proven by the disadvantages that impact the host community if the Inner Baduy is opened up to tourism market. It could cause culture acculturation, a deterioration of morality, environmental damages, and also the decreased quality of local people?s language. For the regional development, the opening up of the Inner Baduy can bring advantages such as improvements of infrastructures and economic benefits. The Inner Baduy is unofficially opened for visits from the tourists but the policy to open it up to mass market depends entirely on the decision of the host community.